Development and Performance Evaluation of a Dryer for Preserving Vegetable Leaves - Jamesmary E. AYANRU; Matthew S. ABOLARIN; Omotayo I. OGUNWEDE; Henry I. MORKAH; Adeshola O. OPENIBO (FUDMA Journal of Engineering and Technology, 2025)
Vegetable leaves need to be well preserved and kept in their best quality to avoid excess wastage when they are out of season, by minimizing pathogenic bacteria that cause decaying. As a result of this search, a machine dryer was created to preserve the vegetable leaves throughout the surplus season. The drying machine has two identical rectangular cabinets with three identical tray plates. It is designed to be electrically powered by means of a circuit box that includes a temperature controller, a contactor, and a switch. A heating filament with 1,800 W capacity serves as the heat source. The developed machine also contained a 12V, 25W DC motor and a propeller shaft connected with fans that extract moisture from the drying materials, such as fluted pumpkin leaf (Telfairia occidentalis), water leaf (Talinum triangulare), and bitter leaf (Vernonia amygdalina). The result shows the mass of water removed during drying of the aforementioned three varieties of vegetable leaves was 3.500 g, 4.387 g, and 3.850 g, respectively, to attain the required moisture content for preservation. The amount of moisture extracted was 72.9%, 75%, and 73.3%. The total heat energy required to extract moisture was 2,858.4KJ, and the efficiency of the developed machine was evaluated to be 70.6%. This implies that the developed machine is capable of drying the three varieties of vegetable leaves used for this study to a required moisture content to avoid waste and reduce high prices when out of season, among other benefits.